1985
DOI: 10.1017/s0016672300021972
|View full text |Cite
|
Sign up to set email alerts
|

Parental influences on X chromosome expression

Abstract: Using mice that were mosaics for both Xce and phosphoglycerate kinase (Pgk-l) alleles, we have established that the parental source of the Xce gene may affect the probability with which the X chromosome carrying it will remain active. This effect was seen in one allelic combination of Xce but not in another. The relationship between these effects and other phenomena of maternal 'imprinting' is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

1986
1986
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 13 publications
4
14
0
Order By: Relevance
“…The direction of the reciprocal cross differences in AKR/J heterozygotes described in Table 1 agrees with that of Forrester & Ansell (1985), although actual percentages differ: they found 52% PGK-1 A (data combined from two groups) when Xce c was of paternal origin compared to 60% in crosses A and C above (P < 0-001) and 60% PGK-1 A (data combined from three groups) when Xce c was of maternal origin compared to 65 % in cross B (P < 0-001) and D (P<001). These data suggest the existence of a fourth allele for Xce carried by the AKR/J mouse strain, subject to parental influences on its expression, but distinct from the ' b ' allele.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…The direction of the reciprocal cross differences in AKR/J heterozygotes described in Table 1 agrees with that of Forrester & Ansell (1985), although actual percentages differ: they found 52% PGK-1 A (data combined from two groups) when Xce c was of paternal origin compared to 60% in crosses A and C above (P < 0-001) and 60% PGK-1 A (data combined from three groups) when Xce c was of maternal origin compared to 65 % in cross B (P < 0-001) and D (P<001). These data suggest the existence of a fourth allele for Xce carried by the AKR/J mouse strain, subject to parental influences on its expression, but distinct from the ' b ' allele.…”
Section: Resultssupporting
confidence: 73%
“…CBA(Pgk-l a ) mice were produced in this laboratory by backcrossing C3Yl(Pgk-l a ) mice onto a CQA./C2L{Pgk-l") background for 20 generations. Pgk-1 and Xce are tightly linked on the X chromosome and no recombination was observed between these loci in our backcrossing programme (Forrester & Ansell, 1985). This observation was confirmed by Krietsch et al (1986), who similarly observed no recombinants after 15 generations of backcrossing.…”
Section: (I) Micesupporting
confidence: 83%
See 3 more Smart Citations